Pengembangan Multimedia Interaktif Berbantuan Aplikasi Articulate Storyline untuk Peserta Didik Kelas III Sekolah Dasar - Faradisa, Zahra (Universitas Negeri Padang, 2024)
This research aims to discuss the development of learning media in the form of interactive multimedia assisted by articulate storyline applications for class III elementary school students. The development model in this research is the ADDIE model through the stages of analysis, design, development, implementation and evaluation. The data for this study were obtained from material expert validation sheets, linguist validation sheets and media expert validation sheets. The results of the material validity test in the development of interactive multimedia assisted by the articulate storyline application obtained a percentage of 84.21%, the language validity test results obtained a percentage of 87.5% and the media validity test results obtained a percentage of 85.71%. While the practicality test results obtained a percentage of 81.25% for the teacher response questionnaire and 95.8% for the student response questionnaire.